(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the official documents created for the development of the city of Khiva in the years of independence of the author are presented. Based on the legal documents, the attention paid by the government to the current state and development of the city, the decisions of the President of the Republic of Uzbekistan, the Cabinet of Ministers, and the essence and importance of state programs and projects are analyzed.